2005
DOI: 10.1007/s00520-005-0841-4
|View full text |Cite
|
Sign up to set email alerts
|

The behaviors of seeking a second opinion from other health-care professionals and the utilization of complementary and alternative medicine in gynecologic cancer patients

Abstract: Seeking a second opinion from other HCP is common in gynecologic cancer patients. Patients who seek a second opinion are more likely to utilize CAM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…After searching through these results, a total of 12 full length papers in English (Gruenigen et al, 2001;Powell et al, 2002;Swisher et al, 2002;Navo et al, 2004;Tam et al, 2005;Molassiotis et al, 2006;Fascing et al, 2007;Akyuz et al, 2007;Finnane et al, 2011;Andersen et al, 2012;Arye et al, 2012;Arye-Ben et al, 2014). Studies which are fulfilling the criteria for this review through such studies obtained from the databased are shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…After searching through these results, a total of 12 full length papers in English (Gruenigen et al, 2001;Powell et al, 2002;Swisher et al, 2002;Navo et al, 2004;Tam et al, 2005;Molassiotis et al, 2006;Fascing et al, 2007;Akyuz et al, 2007;Finnane et al, 2011;Andersen et al, 2012;Arye et al, 2012;Arye-Ben et al, 2014). Studies which are fulfilling the criteria for this review through such studies obtained from the databased are shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…The "Second medical opinion Network" is an innovative tool for patients to actively seek information and be involved in their therapeutic treatment. The demand for such active involvement in medical decisions progressively increased over the years [42,64]. Several studies suggest that about 68% of patients seek a second opinion, so that would get another diagnosis or prognosis, and 65% would assurance regarding the diagnosis or treatment options [44,47,[65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“…This fear may lead patients to avoid discussing the topic with their physician, misleading the physician-patient relationship in the long term; 2) A potential conflict when discrepancies exist between the first and second opinion [49,64].…”
Section: Discussionmentioning
confidence: 99%
“…22 A survey from 2006 of 1,984 US breast cancer patients found that about 20% of them sought a SO. 25 Much higher rates were found in Hong Kong (41.9%), 16 Japan (40.6%), 18 and Israel (45%), 26 but only 6.5% in Australia. 13 Moreover, to the best of our knowledge, all studies that evaluated SO utilization were based on patient self-reported surveys which inherently rely on the patient's subjective interpretation of what is a SO.…”
Section: Introductionmentioning
confidence: 97%
“…[14][15][16] In many cases, patients seek a SO simply because they hope that the diagnosis would turn out to be wrong, 4,17 are anxious about their condition, 4,18 or find it difficult to emotionally deal with the diagnosis. 11,12 Patients also seek a SO when they are dissatisfied with an impersonal communication or feel that their physician had not spent enough time with them, feel they did not get the information they need, or lack trust in the physician.…”
Section: Introductionmentioning
confidence: 99%